2020
DOI: 10.1093/ibd/izz305
|View full text |Cite
|
Sign up to set email alerts
|

Disease Characteristics and Severity in Patients With Inflammatory Bowel Disease With Coexistent Diabetes Mellitus

Abstract: Background Given the rising prevalence of diabetes mellitus (DM) and the limited data on its effect on the course of inflammatory bowel disease (IBD), we characterized multiyear patterns of disease severity in a cohort of IBD patients with coexistent DM. Methods Data of consented IBD patients followed prospectively in a natural history registry at a tertiary center between 2009 and 2017 were analyzed. Patients with ≥3 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Hypoalbuminemia has been described as a negative prognostic factor in several diseases, [89][90][91][92]. Furthermore, low serum albumin concentrations have been shown to be associated with the severity of chronic inflammatory diseases, inflammatory bowel disease and diabetes mellitus [93], cirrhosis [94], as well as with the severity of surgical trauma [95], acute diseases [96] and sepsis [97]. In addition, in past SARS epidemics, hypoalbuminemia has been shown to be related with disease severity and increased hospital mortality [98,99].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoalbuminemia has been described as a negative prognostic factor in several diseases, [89][90][91][92]. Furthermore, low serum albumin concentrations have been shown to be associated with the severity of chronic inflammatory diseases, inflammatory bowel disease and diabetes mellitus [93], cirrhosis [94], as well as with the severity of surgical trauma [95], acute diseases [96] and sepsis [97]. In addition, in past SARS epidemics, hypoalbuminemia has been shown to be related with disease severity and increased hospital mortality [98,99].…”
Section: Discussionmentioning
confidence: 99%
“…Younger IBD patients with microbial disorders are more susceptible to DM than non-IBD patients due to chronic inflammation and increased insulin levels [8]. Increased inflammation and gut microbial dysbiosis lead to both DM and IBD [9,10]. For both disorders, biotherapy research needs to develop incremental treatments with reduced side effects [3,11].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with IBD cohorts, IBD DM patients had significantly higher rates of sepsis and other infections [ 10 ]. Furthermore, a retrospective study that utilized 2810 outpatient cohorts concluded that DM is associated with worse IBD severity reflected by increased use of the emergency room and nearly double the rates of patients with gastrointestinal clinic visits [ 15 ]. While these studies have employed different databases and methodology, one consistent finding with these studies is the overall increase in the odds of infection-related complications among IBD DM patients compared to the IBD cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Given the overlapping impairment in the immune system, concomitant DM is a significant comorbidity among patients with IBD, as reflected by increased hospitalizations [ 15 ]. While our study did not find a significant difference in the length of hospital stay and cost of hospitalization between IBD DM and IBD, we did not explore health care utilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation